OVERCOMING POVERTY TRAP: THE CASE OF WATER & SANITATION IN INDONESIA - Masniarita Pohan, Hilda Leilani (Buletin Studi Ekonomi, 2016)
Overcoming Poverty Trap : The Case of  Water & Sanitation in Indonesia. Poverty trap is a cycle in which poor individuals exhibit low health quality due to malnutrition and limited access to health related facilities. Poor health causes low productivity which eventually cycles back to low income. Indonesia significantly reduced poverty from 15.6% in 1990 to 3.3% in 2010. However, this achievement is not conveyed equally across regions. Using data form RAND Corporation, estimations showed that access to sanitation and clean water play a crucial role in improving one’s health quality.   Keywords: poverty trap, productivity, income, health facility.
Keywords: poverty trap, productivity, income, health facility